Model Pengembangan Kompetensi Mahasiswa dalam Pengembangan Bahan Ajar Digital Pada Program Pendidikan Guru: Studi Kasus Mahasiswa Prodi Pendidikan Guru MI - Nurhidayah, Nurhidayah; Najitama, Fikria (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Social studies education is one of the compulsory subjects given to elementary school (SD) or Madrasah Ibtidaiyyah (MI) students which aims to form good citizens, so that its achievement is highly dependent on the quality of learning they receive in this case the use of teaching materials that suit the student's learning profile.The purpose of this study was to describe the model of student competency development in compiling digital teaching materials for social studies subjects. The approach used in this study is a qualitative approach with case studies. Data collection was carried out through observation, interviews and documentation studies. The results of the study showed that the student competency development model was carried out using democratic participatory techniques, and was differentiated. Students carried out self-development in compiling digital teaching materials through theoretical and practical reinforcement. So that students not only have theoretical knowledge but can also practice. The result is that students are able to develop digital teaching materials that are in accordance with the analysis of content needs and are interesting. The conclusion of the study shows that the competency development model accommodates the uniqueness of students so that the digital learning materials developed are able to adjust the demands of digital-based educational transformation that are interesting, effective and efficient according to the expected learning outcomes.Pendidikan IPS adalah salah satu mata pelajaran wajib yang diberikan pada siswa usia Sekolah Dasar (SD) atau Madrasah Ibtidaiyyah (MI) yang bertujuan untuk membentuk  warga Negara yang baik (good citizen), sehingga dalam pencapaiannya sangat bergantung pada kualitas pembelajaran yang  diterimanya, dalam hal ini penggunaan bahan ajar yang sesuai profil belajar siswa. Tujuan penelitian ini adalah untuk mendeskripsikan  model pengembangan kompetensi  mahasiswa dalam penyusunan bahan ajar digital mata pelajaran IPS. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan studi kasus. Pengumpulan data dilakukan melalui observasi, wawancara dan studi dokumentasi. Hasil penelitian menunjukkan  bahwa model Pengembangan kompetensi mahasiswa dilakukan dengan teknik partisipatif demokratis, dan berdifferensiasi. Mahasiswa melakukan Pengembangan diri dalam penyusun bahan ajar digital  melalui penguatan teoritis dan praktik. Sehingga  mahasiswa tidak hanya memiliki pengetahuan teoritis namun juga bisa melakukan praktik. Hasilnya mahasiswa mampu mengembangkan bahan ajar digital yang sesuai  dengan analisis kebutuhan konten dan menarik. Simpulan penelitian menunjukkan bahwa model pengembangan kompetensi mengakomodir keunikan  mahasiswa sehingga bahan pembelajaran digital yang dikembangkan mampu menyesuaikan tuntutan dalam tranformasi pendidikan berbasis digital yang menarik, efektif dan efisien sesuai capaian pembelajaran yang diharapkan.